The emerging roles of TLR and cGAS signaling in tumorigenesis and progression of ovarian cancer - Zhang, Zhen; Zhao, Hong; Chu, Chu; Fu, Xiaoxiao; Liu, Yonglin; Wang, Li; Wei, Ran; Xu, Ke; Li, Lihua; Li, Xia (Frontiers in Pharmacology, 2022)
Ovarian cancer is fatal to women and has a high mortality rate. Although on-going efforts are never stopped in identifying diagnostic and intervention strategies, the disease is so far unable to be well managed. The most important reason for this is the complexity of pathogenesis for OC, and therefore, uncovering the essential molecular biomarkers accompanied with OC progression takes the privilege for OC remission. Inflammation has been reported to participate in the initiation and progression of OC. Both microenvironmental and tumor cell intrinsic inflammatory signals contribute to the malignancy of OC. Inflammation responses can be triggered by various kinds of stimulus, including endogenous damages and exogenous pathogens, which are initially recognized and orchestrated by a series of innate immune system related receptors, especially Toll like receptors, and cyclic GMP-AMP synthase. In this review, we will discuss the roles of innate immune system related receptors, including TLRs and cGAS, and responses both intrinsic and exogenetic in the development and treatment of OC.